Alterations of the human gut Methanobrevibacter smithii as a biomarker for inflammatory bowel diseases. (April 2018) - Ghavami, Shaghayegh Baradaran; Rostami, Elham; Sephay, Abbas Akhavan; Shahrokh, Shabnam; Balaii, Hedieh; Aghdaei, Hamid Asadzadeh; Zali, Mohammad Reza
Abstract: It is hypothesized that direct and indirect homeostasis between gut microbiota plays a key role in different intestine disorders. Archaea methanogens, an ancient domain of single-celled organism, are major archaea in the digestive system. Recent evidence has shown that the variable prevalence of methanogens in different individuals could have certain effects on inflammatory bowel diseases (IBD). We aimed to assess the prevalence of Methanobrevibacter smithii between Iranian patients suffering from IBD and healthy control subjects. Stool DNA extracts from 47 healthy controls and 61 IBD patients were investigated. Quantitative real time PCR was performed for detecting Mbb. smithii load. We found a significantly decreased the Mbb. smithii load between IBD patients and healthy subjects. It is assumed that there is a reverse association between Mbb. smithii bacterial load and susceptibility to IBD, and this association could be extended to IBD patients in remission as we found that Mbb. smithii bacterial load is markedly higher among healthy subjects in comparison to IBD patients. Highlights: Methanobrevibacter smithii is considered a major member of methanogen archaea. The results of present study showed that the prevalence of Mbb. smithii in stool samples of IBD patients were significantly lower than healthy control subjects (P ≤ 0.001). In addition, when our IBD patients were in clinical remission, we found more Mbb. smithii load than the activity status of the disease (P ≤ 0.06). In addition, the ROC curve showed that Mbb. smithii can be a biomarker in a healthy colon.